Nursing experiences in the event of neonatal death: A phenomenological view - Cárdenas de Fernández, María (2018)
Death is a universal situation that all human beings live throughout their lives, it is difficult to deal with and much more confront the loss of a newborn. This is a situation many times the nursing professional has feelings of guilt, have failed Addressing neonatal death is a delicate task to get the family member to express their emotions, to drain their sadness is very difficult and much more when immersed in their pain, this experience does not leave indifferent to the nursing professionals who do not know how to behave, nor how to accompany and care for a woman and her partner when they have suffered a loss. The objective is to interpret the meanings of the experience experienced by nursing professionals in situations of neonatal death. This research has a phenomenological hermeneutical approach, its paradigm is qualitative and the method used for this study was of Herbert Spiegelberg. The study was carried out at the Ángel Larralde University Hospital "Carabobo Hospital" of Valencia, State Carabobo, Venezuela in the Neonatology Service, it was attended by three nursing professionals and two mothers who lost their son, and an in-depth interview was conducted, obtaining subcategories for later theorization. As a conclusion it is obtained that the nursing professional needs to be prepared before death situations and that is why each moment of the care is unique, and the way in which they are provided will be reflected in the patient and family, however painful may occur.